Case report: Treatment of advanced CSF1-receptor associated leukoencephalopathy with hematopoietic stem cell transplant - Bergner, Caroline G.; Schäfer, Lisa; Vucinic, Vladan; Schetschorke, Birthe; Lier, Julia; Scherlach, Cordula; Rullmann, Michael; Sabri, Osama; Classen, Joseph; Platzbecker, Uwe; Kühl, Jörn-Sven; Barthel, Henryk; et al. (Frontiers in Neurology, 2023)
CSF1R-related leukoencephalopathy is a rare genetic disorder that presents with severe, adult onset white matter dementia as one of the leading symptoms. Within the central nervous system, the underlying mutation affects exclusively microglia cells. Growing evidence implicates that replacing defective microglia by healthy donor cells through hematopoietic stem cell transplant might halt disease progression. Early initiation of that treatment is crucial to limit persistent disability. However, which patients are amenable for this treatment is not clear and imaging biomarkers that specifically depict lasting structural damage are lacking. Here we report on two patients with CSF1R-related leukoencephalopathy in whom hematopoietic stem cell transplant at advanced disease stages led to clinical stabilization. We compare their disease course with that of two further patients admitted in the same timeframe to our hospital, but considered too late for treatment, and place our cases in context with the literature. We propose that rate of clinical progression might be an appropriate discriminator in transplant decisions. Furthermore, for the first time we evaluate in our patients [18F]florbetaben, a PET tracer known to bind to intact myelin, as a novel MRI-adjunct tool to image white matter damage in CSF1R-related leukoencephalopathy. Taken together, our data reinforces evidence for hematopoietic stem cell transplant as a promising treatment in CSF1R-related leukoencephalopathy patients with slow to moderate disease progression rate.